2000
DOI: 10.1111/j.1651-2227.2000.tb02769.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of breathing pattern and ventilation in newborn infants and adult subjects

Abstract: Experimentally modified breathing pattern in human subjects, by varying the inspired gas mixture or administering different neuromodulators, has been studied extensively in the past, yet unmodified breathing has not. Moreover, most data refer to infants during sleep and adults during wakefulness. We studied the baseline breathing pattern of preterm infants [n= 10; GA 30 (27–34) wk (median, range)]; term infants [n= 10; GA 40 (39–41) wk)], and adult subjects [n= 10; age 31 (17–48) y)] during quiet sleep. A flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In animals, a positive long-term correlation of EELV was found in anesthetized rats, suggesting that EELV had fractal properties [19] . In infants, variability of EELV has not been reported previously, whereas variability of respiratory timing and amplitude has been shown to be greater in premature infants in comparison to older infants or adults [15] . Breathing variability is not purely random; a long-range correlation that follows a power-law distribution has been demonstrated for VT and respiratory timing in infants [6,16] .…”
Section: Eelv Variability In Normally Breathing Patientsmentioning
confidence: 81%
See 3 more Smart Citations
“…In animals, a positive long-term correlation of EELV was found in anesthetized rats, suggesting that EELV had fractal properties [19] . In infants, variability of EELV has not been reported previously, whereas variability of respiratory timing and amplitude has been shown to be greater in premature infants in comparison to older infants or adults [15] . Breathing variability is not purely random; a long-range correlation that follows a power-law distribution has been demonstrated for VT and respiratory timing in infants [6,16] .…”
Section: Eelv Variability In Normally Breathing Patientsmentioning
confidence: 81%
“…The active control of EELV implies the flow-breaking action of the larynx [23] and of the diaphragm by its tonic activity [22] , and the respiratory timing pattern with relatively short TE [24] . Both tonic diaphragmatic activity and TE have high intrinsic variability [15,22] . In the present study, important variations of TE and VT were also observed, which may have favored EELV fluctuations.…”
Section: Eelv Variability In Normally Breathing Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…During NREM sleep, the coefficient of variation of minute ventilation is highest in preterm infants (39%), compared with term infants (25%) and adults (14%) (49). Further, peripheral chemoreceptor function, as measured by a 100% oxygen challenge, demonstrates a much larger reduction in minute ventilation in infants (38%) compared with adults (6%), thus contributing to infant ventilatory instability (50).…”
Section: Ontogeny Of Ventilatory Controlmentioning
confidence: 99%